2021
DOI: 10.3390/antibiotics10101152
|View full text |Cite
|
Sign up to set email alerts
|

Piglet Gut and in-Barn Manure from Farms on a Raised without Antibiotics Program Display Reduced Antimicrobial Resistance but an Increased Prevalence of Pathogens

Abstract: In response to new stringent regulations in Canada regarding the use of antibiotics in animal production, many farms have implemented practices to produce animals that are raised without antibiotics (RWA) from birth to slaughter. This study aims to assess the impact of RWA production practices on reducing the actual total on-farm use of antibiotics, the occurrence of pathogens, and the prevalence of antimicrobial resistance (AMR). A 28-month longitudinal surveillance of farms that adopted the RWA program and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…With regard to agriculture and aquaculture practices, 51 antibiotics have been reported as being in use according to the World Health Organization ( WHO, 2017 ), including the six most-common classes of antibiotics: tetracyclines, quinolones, aminoglycosides, polymyxins, macrolides, penicillins, and sulfonamides ( Chekabab et al, 2021 ). It is important to note that antibiotic usage for humans and animals often occurs within similar drug classes (e.g., gentamicin/aminoglycoside, ampicillin/ β-lactams, ciprofloxacin/fluoroquinolones, trimethoprim/antifolate, and tetracycline) ( Finley et al, 2013 ; EUCAST, 2019 ); thus, the potential for cross-resistance to those drugs used in either setting exists.…”
Section: The Role Of Animal Agriculture In Environmental Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…With regard to agriculture and aquaculture practices, 51 antibiotics have been reported as being in use according to the World Health Organization ( WHO, 2017 ), including the six most-common classes of antibiotics: tetracyclines, quinolones, aminoglycosides, polymyxins, macrolides, penicillins, and sulfonamides ( Chekabab et al, 2021 ). It is important to note that antibiotic usage for humans and animals often occurs within similar drug classes (e.g., gentamicin/aminoglycoside, ampicillin/ β-lactams, ciprofloxacin/fluoroquinolones, trimethoprim/antifolate, and tetracycline) ( Finley et al, 2013 ; EUCAST, 2019 ); thus, the potential for cross-resistance to those drugs used in either setting exists.…”
Section: The Role Of Animal Agriculture In Environmental Antibiotic Resistancementioning
confidence: 99%
“…Tetracyclines and macrolides have historically seen extensive use in agriculture (Ebmeyer et al, 2021) and ARGs conferring resistance to these antibiotics are among the most prevalent (Chekabab et al, 2020(Chekabab et al, , 2021. In China, most of the veterinary antibiotics consist of tetracyclines and sulfonamides (Zhou et al, 2020).…”
Section: The Role Of Animal Agriculture In Environmental Antibiotic Resistancementioning
confidence: 99%
“…The impact of antibiotic treatments on the prevalence of pathogens and ARGs in the gut microbiome of piglets and grower-finisher pigs has previously been examined [ 14 , 15 , 16 , 17 ]; however, limited information is available on the potential differential effects of these treatments on the abundance of pathogens and ARGs in the gut and nasal microbiome of sows. The monitoring of antimicrobial usage in the Canadian swine industry through the Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS) is mainly focused on grower-finisher pigs, with no data on sows available [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A subset of the taxonomic profiles belonging to bacterial pathogens was used to identify the total complement of pathogens (the pathome). As described in a study by Chekabab et al [ 14 ], microbes were classified and identified on the species-, subspecies-, and strain-levels. The relative abundance and frequency of the identified organisms were quantified using GenBook comparators and the GENIUS software implemented within the CosmosID algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation